Remnants of the Russian bureaucracy in the public administration of the restored Polish state: Pozostałości biurokracji rosyjskiej w administracji publicznej odrodzonego państwa polskiego - Górak, Artur (Klio - Czasopismo Poświęcone Dziejom Polski i Powszechnym, 2025)
The article is an attempt to draw the attention of researchers to the consequences of the existence of the Russian imperial bureaucracy on the territory of the later Republic of Poland. Bureaucracy is understood here as an objective management tool (law, structure, officials, and documents). The Russian model of the office system was introduced in the administration of the Kingdom of Poland in 1867. The major assumption of the article is that the elements of this system were in operation also in the 20th century. Niniejszy artykuł jest próbą zwrócenia uwagi badaczy na konsekwencje istnienia rosyjskiej biurokracji imperialnej na terytorium późniejszej Rzeczypospolitej. Biurokracja jest tu rozumiana obiektywnie jako narzędzie zarządzania (prawo, struktura, urzędnicy i dokumenty). Rosyjski model biurokratyczny został wprowadzony w administracji Królestwa Polskiego w 1867 r. Główną tezą artykułu jest to, że elementy tego systemu funkcjonowały również w XX w.